Pressure and strain effects of hexagonal rare-earth manganites: a first-principles study. (26th February 2016) - Tan, Hengxin; Xu, Changsong; Li, Menglei; Wang, Shanying; Gu, Bing-Lin; Duan, Wenhui
Abstract: We have investigated the structural, electrical and magnetic properties as well as the phonon modes of hexagonal rare-earth manganites ( R MnO3, R   =  Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Tm and Lu) under chemical pressure, hydrostatic pressure and epitaxial strain by first-principles calculations. The magnetic ground state of R MnO3 is found to have magnetic configuration and to be stable under all considered external conditions. In contrast, the K 3 phonon mode, which is the primary order parameter and responsible for the 'improper ferroelectricity', is greatly influenced by pressure and epitaxial strain. Consequently, the electric polarization is enhanced by 56.7% when the chemical pressure increases from R   =  Pr to R   =  Lu. The hydrostatic pressure can also improve the polarization to a certain degree, e.g. by 14.7% from 0 GPa to 40 GPa in LuMnO3 . Finally, the dependence of polarization on the epitaxial strain is also given, revealing that the compressive strain could promote the ferroelectricity while tensile strain will suppress it.